Life Cycle Assessment of Energy Systems - Miguel, Guillermo San; Alvarez, Sergio (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This Special Issue on "LCA of Energy Systems" contains inspiring contributions on assessing the sustainability of novel technologies destined to shape the future of our energy sector. These include battery-based and plug-in hybrid electric vehicles, geothermal energy, hydropower, biomass gasification, national electricity systems, and waste incineration. The analysis of trends and singularities will be invaluable to product designers, engineers, and policy makers. Furthermore, these exercises also contribute to refining the life cycle framework and harmonizing methodological decisions. Our hope is that this should be a step toward promoting the use of science and knowledge to shape a better world for everyone.